2016
DOI: 10.1007/s00792-016-0875-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analyses of the functions of [NiFe]-hydrogenase maturation endopeptidases in the hyperthermophilic archaeon Thermococcus kodakarensis

Abstract: The maturation of [NiFe]-hydrogenases requires a number of accessory proteins, which include hydrogenase-specific endopeptidases. The endopeptidases carry out the final cleavage reaction of the C-terminal regions of [NiFe]-hydrogenase large subunit precursors. The hyperthermophilic archaeon Thermococcus kodakarensis harbors two [NiFe]-hydrogenases, a cytoplasmic Hyh and a membrane-bound Mbh, along with two putative hydrogenase-specific endopeptidase genes. In this study, we carried out a genetic examination on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…This work presents the first demonstration of cross-species complementation by hydrogenase maturation endopeptidases, highlighting the close evolutionary relationship between group 4 [NiFe]-hydrogenases and demonstrating the critical importance of the HycI-type protease in the biosynthesis of these enzymes. These data are in line with studies showing a endopeptidase for a group 1D hydrogenase was able to activate a different group 1D enzyme within the same organism (Salmonella enterica) [34], and one endopeptidase was able to activate both a group 3B hydrogenase and group 4D hydrogenase within the same organism (Thermococcus kodakarensis) [35].…”
supporting
confidence: 90%
“…This work presents the first demonstration of cross-species complementation by hydrogenase maturation endopeptidases, highlighting the close evolutionary relationship between group 4 [NiFe]-hydrogenases and demonstrating the critical importance of the HycI-type protease in the biosynthesis of these enzymes. These data are in line with studies showing a endopeptidase for a group 1D hydrogenase was able to activate a different group 1D enzyme within the same organism (Salmonella enterica) [34], and one endopeptidase was able to activate both a group 3B hydrogenase and group 4D hydrogenase within the same organism (Thermococcus kodakarensis) [35].…”
supporting
confidence: 90%
“…The structure of immature HyhL reveals that the Cterminal extension of immature HyhL interacts with its β2 strand, adopting a β-strand conformation (the β11 strand). It has been reported that the His424 residue of HyhL at the C-terminal region is a recognition residue for the C-terminal cleavage by its maturation protease HybD (17). The His424 residue is also located in the β11 strand of immature HyhL.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the specific endopeptidase T . kodakarensis HybD cleaves immature HyhL at His424 in the C-terminal extension, which is also located in the β11 strand in the immature HyhL. In the immature state, the recognition site at the C-terminal extension is sterically protected from the endopeptidase by formation of the β11 strand.…”
Section: Recognition Of the Immature Large Subunit Hyhl By Hypamentioning
confidence: 99%
“…Our structures of the HypA-HyhL complex provide a clear understanding of how specific endopeptidases can cleave the C-terminal extension of the large subunit only after the [NiFe] incorporation. It was reported that the specific endopeptidase T. kodakarensis HybD cleaves immature HyhL at His424 in the C-terminal extension, 54 which is also located in the β11 strand in the immature HyhL. In the immature state, the recognition site at the C-terminal extension is sterically protected from the endopeptidase by formation of the β11 strand.…”
Section: ■ Introductionmentioning
confidence: 99%